Oil palm circular mobility and human capital outcomes: strengthening sustainable development goals - Herdis Herdiansyah; Randi Mamola (Sustainable Futures)
The circular mobility of oil palm continues to evolve in tandem with the rapid development of the global supply chain. The mobility of oil palm in developing countries is reportedly beginning to shape the supremacy of farmers’ capacity building by pursuing the strengthening of human capital to influence sustainable human resources. This study examines the correlation between the circular mobility of oil palm and human capital outcomes, such as farm labor attendance, school participation, health status, and consumption purchasing power. Our research introduces income pathway as a contribution to the correlation analysis of the full-scale strengthening of farmers’ human capital outcomes. Our data set utilizes three rounds of household surveys for production and non-production farmers within the oil palm growth zone in the Indonesian province of North Sumatra, South Sumatra, Central Kalimantan, and West Kalimantan. Using two-stage least squares regression analysis and Spearman correlation, findings indicate positive evidence of a correlation among the circular mobility of oil palm, farm labor attendance, and school participation. This research discovers a negative relationship between health status and farmers’ consumption purchasing power in the involvement of circular mobility of oil palm. Strengthening the consumption of production and non-production farmers reinforces the correlation with differences in health status measured by infant mortality and nutritional adequacy, strengthening farmers’ consumption purchasing power. The current study finds that farmers’ income determines the level of enhancing their human capital actively engaged in the economic benefits of the circular mobility of oil palm activities so as to increase the achievement of sustainable development goals. Findings reinforce the implications of whether or not the circular mobility of oil palm can penetrate sustainable production, distribution, and consumption, particularly in strengthening the welfare of intragenerational farmers’ human capital.